Problems of accessibility of higher engineering education for students with special needs - Bratanovskii, Sergei; Dustnazar Khimmataliev, Irina Rezanovich, Yulia Bogdanova, Raissa Orsayeva, (Opción)
The article is devoted to studying the problems of accessibility of higher engineering education for people with disabilities and persons with disabilities (PWD), i.e. persons with special learning needs (SLN). Vocational education in modern conditions is becoming a social elevator, giving people with disabilities and disabilities an opportunity for socialization and employment. Studying foreignexperience reveals the effectiveness of inclusive education. The article describes the current state of inclusive higher education, including engineering, in foreign countries (USA, Austria, Finland, etc.) and Russia. The successful practices of training people with higher education in foreign universities are presented. The characteristic of modern trends in the development of inclusive education in the Russian Federation is fulfilled. The criteria of affordable education in a world practice are highlighted in order to compare and evaluate its effectiveness in the Russian Federation. The advantages and disadvantages of the existing training system for disabled people and people with disabilities in Russian practice are noted. Weak demand for engineering specialties in universities of the Russian Federation was revealed. A study of the causes of this phenomenon.